Pengaruh Keterlibatan Kerja, Budaya Organisasi dan Motivasi Kerja terhadap Kepuasan Kerja Pegawai - Yakup Yakup (Perisai : Islamic Banking and Finance Journal, 2017)
This study aims to examine and analyze the effects of job involvement, organizational culture and work motivation on employee satisfaction. The sample size in this study was 53 employees Community Empowerment Board and Bone BolangoRegency Village Government determined by saturation sampling techniques. The collection of data by distributing questionnaires using 5-point Likert Scale to measure the grain of the four variables studied statement. The analysis technique used is multiple linear regression analysis. The results showed that partially, work engagement, organizational culture and work motivation positive effect on employee satisfaction and the Community Empowerment Board Bone Bolango Regency Village Government. In addition, approximately 52 percent of the variation employee satisfaction can be explained by work engagement, organizational culture and work motivation, while the remaining 48 percent is contributed by other variables not included in this research model.